2004
DOI: 10.1021/cm049230t
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Electronic Structure between Cobalt and Oxide Ions of Lithium Cobalt Phosphate as 4.8-V Positive Electrode Material

Abstract: Insight into electron exchange in LiCoPO4 electrodes for high-voltage lithium ion battery is presented using X-ray absorption spectroscopy (XAS). Despite the formation of the isolated valence electrons around the Co ion, O K-edge XAS reveals clear evidence that the hybridized orbital between Co and O plays an important role in the electron exchange arising from the electrochemical Li extraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 9 publications
7
43
0
1
Order By: Relevance
“…The calculated pattern matches the observed one quite well, implying the reliability of the refinement. The refinement reveals lattice parameters of a ¼ 1.0201 (2) nm, b ¼ 0.5923 (1) nm, c ¼ 0.4700 (5) nm, and accordingly V ¼ 284.01 nm 3 for LCPdeposition, in good agreement with previous reports [4,7,12]. The other two samples exhibit rather similar lattice parameters, signifying that carbon coatings exert little impact on the olivine structure.…”
Section: Structuresupporting
confidence: 88%
“…The calculated pattern matches the observed one quite well, implying the reliability of the refinement. The refinement reveals lattice parameters of a ¼ 1.0201 (2) nm, b ¼ 0.5923 (1) nm, c ¼ 0.4700 (5) nm, and accordingly V ¼ 284.01 nm 3 for LCPdeposition, in good agreement with previous reports [4,7,12]. The other two samples exhibit rather similar lattice parameters, signifying that carbon coatings exert little impact on the olivine structure.…”
Section: Structuresupporting
confidence: 88%
“…However, studies on LiCoPO 4 are scarce because the existing preferred nonaqueous electrolytes are found to be unstable in the high-voltage range (≥4.8 V) where cobalt reduction/oxidation reactions can occur. Efforts toward improving nonaqueous electrolytes have made LiCoPO 4 an attractive cathode to explore in the high charge voltage regime, up to 5 V. Although the reversibility of lithium extraction-insertion from/into LiCoPO 4 was demonstrated in a few reports [9][10][11][12], a severe capacity fading during cycling has limited the use of this material in practical applications. As result, less attention has been paid toward the development of LiCoPO 4 cathode in lithium batteries using nonaqueous electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the XRD results showed that the crystalline phase was only a lithiumpoor phase; no "CoPO 4 " phase was identified even though LiCoPO 4 was fully charged. In addition, two successive voltage plateaus were often observed during the charge of LiCoPO 4 [5,[11][12][13][14]. Nakayama et al [13] proved that it was not related to the irreversible side reactions and suggested that it might be due to an increase in electrochemical polarization around x = 0.3 in Li 1−x CoPO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, two successive voltage plateaus were often observed during the charge of LiCoPO 4 [5,[11][12][13][14]. Nakayama et al [13] proved that it was not related to the irreversible side reactions and suggested that it might be due to an increase in electrochemical polarization around x = 0.3 in Li 1−x CoPO 4 . Nevertheless, the exact mechanism for the two-plateau charge profile is still controversial, and in other cases, a one-plateau charge profile was reported [15][16][17].…”
Section: Introductionmentioning
confidence: 99%